The Role of the WTO in Global Trade and its Implications for Developing Economies - Rohmatul Laily Al Faiqoh; Adinda Selvina Adhani; Nur Kholis (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Global trade has long been promoted as a driver of economic growth and international cooperation. The World Trade Organization (WTO), established to ensure fairness and stability in global trade, plays a central role in shaping trade relations among nations. However, concerns persist regarding its impact on developing countries. This study aims to examine how WTO policies influence economic inequality and structural dependency in developing economies. Using a qualitative research approach, this article integrates legal and economic perspectives to analyze relevant literature and assess the WTO's institutional mechanisms. The findings reveal that, although the WTO seeks to promote equitable trade, its policies tend to favor developed countries through liberalization and intellectual property regimes that restrict policy flexibility in developing nations. These mechanisms reinforce technological dependency, reduce competitiveness, and perpetuate unequal participation in global markets. The study concludes that without institutional reform, the WTO framework will continue to sustain global trade imbalances. This article proposes alternative solutions, including enhancing regional and South–South trade cooperation, promoting fair technology transfer, and reforming the WTO's decision-making structures. These measures could foster a more inclusive and balanced trading system that supports sustainable development in the Global South.